Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1017/s1461145709000327
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between subjective well-being and dopamine D2 receptors in patients treated with a dopamine partial agonist and full antagonist antipsychotics

Abstract: Antipsychotic drugs produce unpleasant subjective experiences, which have been associated with high levels of dopamine D2 receptor occupancy. Aripiprazole is a partial agonist antipsychotic, which is hypothesized to produce a different subjective experience profile compared to standard D2 antagonist antipsychotics. The aim of this study was to compare the effect of D2 occupancy produced by a partial agonist antipsychotic (aripiprazole) to that of antagonist antipsychotics (risperidone or olanzapine) on the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
4
45
1
Order By: Relevance
“…In line with Mizrahi et al [38], this study showed that aripiprazole increased subjective well-being and hedonia more than a strong DA antagonist [33]. Moreover, aripiprazole has also shown good treatment effects on depression and bipolar disorder [39,40], and the same receptor effects may alleviate or stabilize (an)hedonic mood [40].…”
Section: Discussionsupporting
confidence: 84%
“…In line with Mizrahi et al [38], this study showed that aripiprazole increased subjective well-being and hedonia more than a strong DA antagonist [33]. Moreover, aripiprazole has also shown good treatment effects on depression and bipolar disorder [39,40], and the same receptor effects may alleviate or stabilize (an)hedonic mood [40].…”
Section: Discussionsupporting
confidence: 84%
“…from risperidone or olanzapine showed improvement in their subjective well-being despite very high levels of D 2 occupancy (Mizrahi et al, 2009). The lack of significant changes in negative symptoms following amisulpride administration may be related to its limbic selectivity (Bressan et al, 2003) and fast dissociation [42 s for 4 nmol/l S-(-)-amisulpride] (Seeman, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the partial dopamine agonistic properties of aripiprazole, as opposed to the dopamine antagonistic properties of other antipsychotics, have a more favorable effect on subjectively experienced side effects [Liemburg et al 2011;Mizrahi et al 2009;Ohlsen and Pilowsky, 2005]. These studies, however, lack ecological validity because emotional experiences were assessed retrospectively and globally using cross-sectional instruments.…”
Section: Discussionmentioning
confidence: 99%